Marijuana use and perinatal outcomes in obstetric patients at a safety net hospital. (November 2021) - Sasso, Elizabeth B.; Bolshakova, Maria; Bogumil, David; Johnson, Brittney; Komatsu, Emi; Sternberg, Jennifer; Cortessis, Victoria; Mullin, Patrick
Abstract: Objective: To characterize the association between antepartum marijuana exposure and maternal and neonatal outcomes at our institution. Study Design: Retrospective chart review identified an obstetric cohort of singleton gestations. Women with self-reported marijuana use were compared with non-users. Demographic characteristics, risk factors, and maternal-fetal outcomes were evaluated. Associations between outcomes and marijuana use were assessed with regression analysis. Results: Of 2792 deliveries, 5.4% reported marijuana use. Compared to non-users, marijuana users entered prenatal care later, were younger, non-Hispanic, and used other illicit substances. Marijuana users had a higher rate of cesarean delivery (p = 0.01). After adjusting for confounders, marijuana use remained associated with 4.1-fold risk of delivering a small for gestational age (SGA) infant and 2.89-fold risk of neonatal oxygen use. Conclusion: At a safety net hospital, antepartum marijuana use is significantly associated with cesarean delivery, SGA and supplemental oxygen use at birth. Healthcare disparities associated with marijuana use make this a population of critical interest.